Segmentasi Multi Proyeksi pada Citra Cone Beam Computed Tomography Gigi Menggunakan Metode Level Set - Fahmi Syuhada; Rarasmaya Indraswari; Agus Zainal Arifin; Dini Adni Navastara (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2021)
Segmentation of dental Cone-beam computed tomography (CBCT) images based on Boundary Tracking has been widely used in recent decades. Generally, the process only uses axial projection data of CBCT where the slices image that representing the tip of the tooth object have decreased in contrast which impact to difficult to distinguish with background or other elements. In this paper we propose the multi-projection segmentation method by combining the level set segmentation result on three projections to detect the tooth object more optimally. Multiprojection is performed by decomposing CBCT data which produces three projections called axial, sagittal and coronal projections. Then, the segmentation based on the set level method is implemented on the slices image in the three projections. The results of the three projections are combined to get the final result of this method. This proposed method obtains evaluation results of accuracy, sensitivity, specificity with values of 97.18%, 88.62%, and 97.61%, respectively.